2019
DOI: 10.1002/ange.201911554
|View full text |Cite
|
Sign up to set email alerts
|

A 3.3 Å‐Resolution Structure of Hyperthermophilic Respiratory Complex III Reveals the Mechanism of Its Thermal Stability

Abstract: Respiratory chain complexes convert energy by coupling electron flow to transmembrane proton translocation. Owing to a lack of atomic structures of cytochrome bc1 complex (Complex III) from thermophilic bacteria, little is known about the adaptations of this macromolecular machine to hyperthermophilic environments. In this study, we purified the cytochrome bc1 complex of Aquifex aeolicus, one of the most extreme thermophilic bacteria known, and determined its structure with and without an inhibitor at 3.3 Å re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
(18 reference statements)
2
2
1
Order By: Relevance
“…Overall, the T 50 15 and T m of the “best” mutant Km AKR M13 were 6.3 and 10.4°C higher than those of Km AKR M9 , respectively. The CD spectra analysis demonstrated that the “best” mutant Km AKR M13 retains more α ‐helixes as compared with Km AKR M9 at elevated temperature, implying that the increased stability of the α ‐helixes in Km AKR M13 is related with the significantly enhanced thermostability of the enzyme, which is consistent with the report that α ‐helix stabilization is an important feature of highly thermostable enzymes (Brito e Cunha et al, 2019; H. L. Liu & Wang, 2003; Zhu et al, 2020). Additionally, MD simulations of Km AKR M9 and Km AKR M13 performed at 60°C showed that Km AKR M13 retained its structural stability during the 20 ns simulations whereas Km AKR M9 began to lose its structural stability after 5 ns simulations (Figure 6).…”
Section: Discussionsupporting
confidence: 86%
“…Overall, the T 50 15 and T m of the “best” mutant Km AKR M13 were 6.3 and 10.4°C higher than those of Km AKR M9 , respectively. The CD spectra analysis demonstrated that the “best” mutant Km AKR M13 retains more α ‐helixes as compared with Km AKR M9 at elevated temperature, implying that the increased stability of the α ‐helixes in Km AKR M13 is related with the significantly enhanced thermostability of the enzyme, which is consistent with the report that α ‐helix stabilization is an important feature of highly thermostable enzymes (Brito e Cunha et al, 2019; H. L. Liu & Wang, 2003; Zhu et al, 2020). Additionally, MD simulations of Km AKR M9 and Km AKR M13 performed at 60°C showed that Km AKR M13 retained its structural stability during the 20 ns simulations whereas Km AKR M9 began to lose its structural stability after 5 ns simulations (Figure 6).…”
Section: Discussionsupporting
confidence: 86%
“…We originally hypothesized it would be caused by formation of a supercomplex between AaC c O and complex III, providing additional quinol binding sites for its direct oxidation bypassing cytochrome c . However, our structural study of the A. aeolicus complex III [20] does not support this hypothesis. Furthermore, our substantial image processing of the current purified sample does not suggest the existing of any potential supercomplex (Figure S2).…”
Section: Resultscontrasting
confidence: 72%
“…In our previous study of A. aeolicus complex III, we discovered an extra transmembrane helix of cyt. c 1 and several unique residues important for the thermostability of the complex [20] . Interestingly, we also found that subunit I of AaC c O possesses two additional C‐terminal transmembrane helices, THM13 and TMH14, in comparison with eukaryotic C c Os, or still one additional TMH when comparing with TtC c O, a thermophilic prokaryotic C c O.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Based on cryo‐EM 3D classification using RELION [21] (Figure S2), we found two well‐aligned classes of particles existing in the current purified sample. The first class represents the structure of dimeric complex III reported by us before [20] and the second represents the structure of dimeric AaC c O. Our substantial image processing does not suggest the existing of any potential supercomplex in this sample.…”
Section: Resultsmentioning
confidence: 77%